Politicalha de aldeia": os criminalizados do Estado Novo no Oeste de Santa Catarina à luz dos processos-crime do Tribunal de Segurança Nacional - Mayer, Leandro (2020)
The purpose of this study is to investigate, through a set of police inquiries instituted against individuals established in the west of Santa Catarina, whose records were transformed into criminal proceedings before the National Security Court in Rio de Janeiro, the repressive measures resulting from the campaign of nationalization in that physiographic zone during the Estado Novo (1937-1945). The west of Santa Catarina, the spatial delimitation of the study, felt deeply the effects of the actions of the nationalization campaign, as it registered, from the beginning of the 20th century, an intense process of settlement of colonies of German and Italian (i)migrants. These "denationalized" nuclei were seen, in the eyes of the Vargas government, as "ethnic cysts" and accused of transmitting foreign ideologies that put the country's national security at risk, therefore they needed to experiment with nationalist measures and should be fought and assimilated. Based on the understanding that the theme of nationalization is closely related to immigration and ethnic identity, we find in the criminal processes important elements to understand how the nationalization process reached the interior communities, revealing how the repressive measures (institutionalized) of the nationalization campaign were felt by the population of the State of Santa Catarina. In this context, the criminal proceedings of the TSN are the materialization of the repressive action introduced through the authoritarian policy of the Estado Novo. In theory, the course of the proceedings used to be identical: it began with a police inquiry and culminated in the TSN, where the records were transformed into criminal proceedings. In common, the "village politicalha": the Police counted on the denunciations and denunciations that erupted within the communities, where intrigues, misunderstandings, quarrels and banal disaffection resulted in rigorous police investigations, which, in turn, reached the Egregious Court of Security Nacional, a condemnatory court for communists and integralists, which acted as a political-legal instrument and legitimized the repressive and authoritarian practices of the Vargas government.